Perubahan Ekonomi Global dan Tantangan bagi Indonesia [Global Economic Change and Challenges for Indonesia] - Ignatius Ismanto; Roy Vincentius Pratikno (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2016)
The shifting of global political-economy since early 1990s has been followed by the expansion of regional economy cooperation forum establishment, such as: NAFTA (North America Free Trade Area), EFTA (European Free Trade Area) and APEC (Asia Pacific Economic Cooperation). Indonesia, together with the other South East Asia countries who join ASEAN (Association of Southeast Asia), is also actively involved in engaging regional economy cooperation forums, such as: ASEAN-China FTA, ASEAN-India FTA, ASEAN-Jepang Economic Partnership, ASEAN Regional Economi Partnership (ARCEP). The establishment of those economic regionalism is apparently a strategy in responding economical globalization. Indonesia’s involvement in those regional economy cooperations has increased its national commitment, both in going through economical liberization as well as in building its national economy competitiveness. This research describes Indonesian political challanges in responding the dynamic changes of that global economy.